Strategi Penguatan Daya Saing Usaha Pisang Caramel Melalui Inovasi Rasa, Branding, Pemanfaatan Platform Digital dan Pencatatan Keuangan Sederhana - Zahrotul Laila, Isna; Nur Latifah, Salma; Setiawan, Doni; Muniroh, Hetty (Education and Talent Development Center of Indonesia, 2025)
Caramel Legendz Banana is a snack business made from bananas wrapped in skin with sugar and chocolate powder filling, then fried until crispy. This business has great potential but still faces various problems, such as the absence of a banner or a clear business name so that it is not well known to buyers, the packaging is still simple and not attractive, the absence of a menu list with prices, the absence of new flavor innovations, financial records that are not routine, and promotions that only rely on sales at the location without the support of other media. To overcome this, mentoring activities were carried out by students which included making banners and business names, improving packaging design, compiling menu lists, developing new flavor variants, simple financial recording training, and promotions through registering business locations on Google Maps so that they are more easily accessible and known to the public. The results of the activities showed significant changes, namely that the business now has a clearer identity, more attractive product packaging, a menu list that helps buyers, new flavor variants that increase consumer interest, financial records that are starting to be implemented more regularly, and promotions that are increasingly widespread thanks to their presence on Google Maps. Overall, this mentoring has succeeded in improving the quality and competitiveness of the business, helping to strengthen management, and supporting Caramel Legendz Banana so that it is better known and able to develop independently.